Choipan Isi Daun Genjer dan Ebi Cincang dengan Saus Cabai di Kazuki Resto Cipadung Ujung Berung Bandung - Mayang Parameswari; Ida Hafidah (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
Kazuki Resto is an Eastern-themed café and restaurant located at Jl. Raya A.H Nasution No. 39A, Bandung, open from 11:00 AM to 11:00 PM. To diversify the menu, the author introduces choipan, a Chinese snack made from genjer leaves (Limnocharis flava) and minced shrimp. The term "choipan," derived from Hakka, means "vegetable cake," utilizing genjer leaves that are rich in nutrients such as vitamin C, potassium, calcium, and phosphorus. This study aims to evaluate the panelists' preferences for genjer and shrimp-filled choipan with chili sauce, as well as analyze the standard recipe and nutritional value of the product. The method used is research and development, with data collection through organoleptic tests involving 25 panelists, including experts from various backgrounds. The results indicate a favorable preference level, with presentation scores of: appearance 84%, color 84%, aroma 72%, texture 88%, and taste 84%. The standard recipe for choipan includes 60 grams of rice flour, 30 grams of tapioca flour, 150 ml of water, 55 ml of oil, and other ingredients. Nutritional analysis shows an energy value of 40.9 calories, protein 1.31 g, fat 2.03 g, and vitamin C 13.86 mg. The author recommends using fresh, high-quality genjer leaves to avoid bitterness.